TYPHOID AND CHOLERA CHRONICLES: THEIR DUAL EFFECT ON LIFE EXPECTANCY IN DELTA STATE, NIGERIA - Erhuotor, E. E.; Eggon, H. A.; Ajidani, M. S.; Osekweyi, J. O. (FUDMA JOURNAL OF SCIENCES, 2023)
This study investigates Typhoid and Cholera Chronicles: their dual effect on Life Expectancy in Delta state, Nigeria. The Cost of Illness Theory serves as the theoretical framework for this study. Data for the research were primarily gathered through questionnaires administered to 345 respondents. Logistic regression models analyzed using Statistical Package for Social Science (SPSS) v23 were employed to test the relationship between the predictors: namely Typhoid (TYR), and Cholera (CHR), and the dependent variable: life expectancy (LEX). The findings revealed a statistically significant and negative relationship between Typhoid Rate (TYR), and Cholera Rate (CHR), and life expectancy (LEX) in Delta State. This research concludes that Typhoid (TYR), and Cholera (CHR), have a profound effect on life expectancy (LEX) in Delta state. Consequently, it is recommended that vaccination programs be integrated into routine immunization strategies. Moreover, Delta State should prioritize sanitation improvements and access to clean water sources. Investments in proper sewage disposal and the provision of safe drinking water, particularly in underserved areas, are essential. These improvements will not only reduce the economic burden but also enhance public health and well-being.
Keywords: Water-Borne Diseases; Typhoid; Cholera; Life expectancy